1983
DOI: 10.1007/bf00291539
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic evidence for three human X-chromosomal segments escaping inactivation

Abstract: Early replication of prometaphasic human sex chromosomes was studied with the bromodeoxyuridine (BrdU)-replication technique. The studies reveal that two distal segments of Xp, including bands Xp 22.13 and Xp 22.3, replicate early in S-phase and therefore may not be subject to random inactivation. Furthermore, the replication of these distal segments of Xp occurs synchronously with those of the short arm of the Y chromosome including bands Yp 11.2 and Yp 11.32. These segments of Xp and Yp correspond well to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Filters were washed with 2 X SSC/0.1%SDS, 1 X SSC/0.1%SDS, 0.1 X SSC/0.1%SDS 10 min each at 65 8C and autoradiographed at K70 8C for 2-5 days. Chromosome preparations were made from peripheral blood according to standard methods with minor modifications (Schempp & Meer 1983). Chromosome FISH was performed as previously described with minor modifications (Wilcox et al 1996).…”
Section: Bac Library Screening and Chromosomal Mappingmentioning
confidence: 99%
“…Filters were washed with 2 X SSC/0.1%SDS, 1 X SSC/0.1%SDS, 0.1 X SSC/0.1%SDS 10 min each at 65 8C and autoradiographed at K70 8C for 2-5 days. Chromosome preparations were made from peripheral blood according to standard methods with minor modifications (Schempp & Meer 1983). Chromosome FISH was performed as previously described with minor modifications (Wilcox et al 1996).…”
Section: Bac Library Screening and Chromosomal Mappingmentioning
confidence: 99%
“…Cytological Methods. Air-dried chromosome preparations were made from peripheral blood according to standard methods with minor modifications (36).…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…However, X chromosome inactivation is a complicated subject. For example, del(X)(p21) is a region of early replication on the inactivated X chromosome and involves some genes which may escape inactivation (29). It has been suggested that complete pairing of X chromosomes may be essential for the survival of oocytes and for the development of ovaries (21,30).…”
Section: Discussionmentioning
confidence: 99%